Data requirement and partnerships for creating and sustaining Dtreo - Teviotdale, Mark; Santos, Bruno; Getachew, Tesfaye; Rischkowsky, Barbara A.; Rekik, Mourad; Solomon, Dawit; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The International Center for Agricultural Research in the Dry Areas (ICARDA) partnering with Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) and the National Agricultural Research Systems (NARS) has been working to develop and sustain a digital database system on the ongoing sheep and goat community-based breeding programs (CBBPs) being implemented in Ethiopia since 2010 (Haile et al., 2018). Currently, a total of about 40 CBBPs each with average of 80 household and 1000 flock size in four sheep (Menz, Bonga, Doyogena and Horro) and three goat (Abergelle, konso and Borena) breeds are available (Haile et al., 2019). Many other CBBPs have also been established throughout the country by different institutions (Research Centers, Universities, and Biodiversity Institute), Africa (e.g. Tanzania, Sudan, Uganda, Malawi) and elsewhere (e.g Brazil, Iran, Mongolia) (Haile et al., 2019).